Role of the River in Twain´s Fiction - Kadeřávková, Lucie (Univerzita Pardubice, 2012)
These papers are focused on the analysis of Mark Twain´s Life on the Mississippi and The Adventures of Huckleberry Finn with respect to the importance of the river of Mississippi. The opening part of these papers introduces literary terms such as realism, local color, regionalism and southern literature. The next section is dedicated to the river from the historical point of view, what happenings had cardinal relevance for the river. The main part of the work is a detailed analysis of the significance of the river in selected novels, which is supported by authentic quotations. The analysis also concentrates on the relationship of the main characters and the author to the Mississippi River, and as a conclusion a comparison of what both the novels have in common concerning the importance of the river and what they differ in.
Role řeky v dílech Marka Twaina
Keywords: Twain, Mark; řeky; Mississippi; jižanská literatura; regionalismus; krajina; rivers; southern literature; regionalism; countryside